IL-13 signaling in cDC2 is required for systemic anaphylactic responses - Yasuyo Harada; Takanori Sasaki; Kazushige Obata-Ninomiya; Takahiro Matsuyama; Satoshi Ueha; Shigeyuki Shichino; Takashi Watanabe; Shuhei Ogawa; Sewon Ki; Yoshie Suzuki; Naoto Ito; Yasutaka Motomura; et al. (Proceedings of the National Academy of Sciences, 2026)
Cutaneous allergen sensitization (CAS) is a primary driver of atopic dermatitis (AD) and a key initiator of the “atopic march”, which can lead to systemic conditions such as food allergy and anaphylaxis. The type 2 cytokine interleukin-13 (IL-13) is an important regulator of high-affinity IgE antibodies, yet the precise cellular targets and mechanisms by which it orchestrates systemic allergic responses remain incompletely understood. Here, we evaluated the role of IL-13 in a murine CAS model that links skin inflammation to systemic anaphylaxis. Using cell-specific deletions of the IL-13 receptor α1 subunit ( Il13ra1 ), we identify conventional dendritic cells (cDCs), and not T or B cells, as the essential targets of IL-13 for generating high-affinity IgE. Single-cell transcriptomics reveal that IL-13 signaling acts specifically in a cDC2 subset characterized by high expression of CX3CR1, Clec10a (CD301a), and CD301b (Mgl2). Licensing by IL-13 endows these cDC2 with superior antigen-presenting capacity, characterized by the upregulation of MHC class II and costimulatory molecules, including CD301a, CD301b, and ICOSL. These mature cDC2s are mobilized from the periphery to the spleen by a CX3CR1-dependent mechanism, where they are uniquely equipped to induce the differentiation of IL-13-producing T follicular helper (T FH 13) cells. This cascade results in robust germinal center reactions and production of pathogenic, high-affinity IgE. Our findings define an IL-13–cDC2 axis that functions as a critical regulator of the atopic march, providing a mechanistic rationale for the clinical efficacy of IL-13-targeted therapies in allergic diseases.